Digital Communication and Social Change Aqiqah Services During The Covid-19 pandemic - Hendri Noviyanto; Jeratallah Aram Dani (INJECT (Interdisciplinary Journal of Communication), 2022)
Aqiqah is an order for Muslims to be grateful for the blessings of Allah because they have entrusted a baby. In Indonesia, Aqiqah has become a business field for Aqiqah services such as livestock sales and meat processing services. However, during the COVID-19 pandemic, Aqiqah services experienced a decline in enthusiasts. This is due to the fear of transmitting the Covid-19 virus when visiting farmers sometimes. This study aims to analyze the effect of digital communication during the covid-19 pandemic on the sale of livestock for Aqiqah. So that the social changes that occur can still be overcome. The research method for the data collection process uses observation, interview, and documentation techniques. The data obtained were processed using validity and reliability techniques. Data analysis used the T-Test technique. The results of the study were assisted by SPSS software to analyze results. Of the 32 questions, 16 questions were obtained that were ready to be tested after going through the validation and reliability tests. The questionnaire was tested on 32 respondents with the results processed using the One-Sample Kolmogorov-Smirnov Test technique, the Absolute value (D) was 0.242, this value is smaller than the table value of 1.7, so the data is said to be normally distributed. Test scores on Levene's Sig. of 0.397 states that the data have the same variance, while the T-Test value on Asymp. Sig. (2-tailed) of .000 which states that using digital media is enough to affect the results of livestock sales.